2010
DOI: 10.2134/agronj2009.0380
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use Efficiency and Nitrogen Fertilizer Recovery of Durum Wheat Genotypes as Affected by Interspecific Competition

Abstract: A gronomy J our n al • Volume 102 , I s sue 2 • 2 010 707 O ver the last four decades, N fertilization has been an essential tool for increasing crop yield and quality, especially for cereals, and for ensuring maximum economic yield (Hirel et al., 2001). However, the energetic cost of synthesizing N fertilizers is very high (Smil, 2001), and N fertilization oft en represents the most expensive energy input in cereal-based cropping systems (Crews and Peoples, 2004). Moreover, because of its high mobility in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
45
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 49 publications
16
45
2
2
Order By: Relevance
“…The density of 15 plants of wild mustard m -2 decreased the spike number by 18.2, 21.2 and 35.1 % under 90, 150 and 210 kg N ha -1 respectively. Our results are corroborating with Giambalvo et al (2010). They stated that the interspecific competition of weed, Hordeum vulgare L. decreased the spike number of wheat (Triticum durum Desf Var.…”
Section: Number Of Tillers and Spikes Per Square Metersupporting
confidence: 92%
“…The density of 15 plants of wild mustard m -2 decreased the spike number by 18.2, 21.2 and 35.1 % under 90, 150 and 210 kg N ha -1 respectively. Our results are corroborating with Giambalvo et al (2010). They stated that the interspecific competition of weed, Hordeum vulgare L. decreased the spike number of wheat (Triticum durum Desf Var.…”
Section: Number Of Tillers and Spikes Per Square Metersupporting
confidence: 92%
“…However, the rainy conditions result in pathological problems in the plant, causing the lower yield in 2012. The use efficiency (NUtE) values were in the range measured in modern durum wheat varieties in other experiments (Giambalvo et al, 2010). The seasonal trend of the three years, with higher values of rain, was favourable for the use of nitrogen, as found from López-Bellido (2012).…”
Section: Discussionsupporting
confidence: 69%
“…This could probably be attributed to the inability of plants to assimilate all of nitrogen taken up. Similar result was reported by a researcher who indicated that nitrogen use efficiency decreased with the increase of nitrogen rate because the plants were unable to assimilate all of nitrogen taken up [3]. Furthermore, nitrogen caused highly significant differences in crude protein and crude fiber content in both seasons.…”
Section: Effect Of Nitrogen On the Yield Nitrogen Use Efficiency Andsupporting
confidence: 87%
“…Nitrogen use efficiency parameters are high under low nitrogen levels and decrease with increasing nitrogen level. Decreased nitrogen use efficiency at high nitrogen is attributed to higher losses because the plant is unable to absorb all of nitrogen applied [3]. Maize is nitro positive and needs ample quantity of nitrogen to attain high yield.…”
Section: Introductionmentioning
confidence: 99%